2024
DOI: 10.1186/s40246-024-00603-x
|View full text |Cite
|
Sign up to set email alerts
|

Altered skin microbiome, inflammation, and JAK/STAT signaling in Southeast Asian ichthyosis patients

Minh Ho,
Huynh-Nga Nguyen,
Minh Van Hoang
et al.

Abstract: Background Congenital ichthyosis (CI) is a collective group of rare hereditary skin disorders. Patients present with epidermal scaling, fissuring, chronic inflammation, and increased susceptibility to infections. Recently, there is increased interest in the skin microbiome; therefore, we hypothesized that CI patients likely exhibit an abnormal profile of epidermal microbes because of their various underlying skin barrier defects. Among recruited individuals of Southeast Asian ethnicity, we perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…There are no current JAK3 mutations associated with microbiome studies aside from a solitary paper correlating skin microbiome with the Jak-Stat pathways [23]. In order to elucidate the presence of a JAK3-altered microbiome, we were able to define the microbiome in one APC patient with the seminal JAK3 mutation and one patient with a variant of the Lynch Syndrome, the Muir-Torre Syndrome who did not have a JAK3 mutation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are no current JAK3 mutations associated with microbiome studies aside from a solitary paper correlating skin microbiome with the Jak-Stat pathways [23]. In order to elucidate the presence of a JAK3-altered microbiome, we were able to define the microbiome in one APC patient with the seminal JAK3 mutation and one patient with a variant of the Lynch Syndrome, the Muir-Torre Syndrome who did not have a JAK3 mutation.…”
Section: Resultsmentioning
confidence: 99%
“…There are multiple studies of CRC in the African American population most recently reviewed by Carethers [23] showing that most studies show more proximal neoplasia and more advanced neoplasia on the right-side of the colon with greater lesion aggressiveness and poorer prognosis. Not all studies showed significant genetic changes in AA (African Americans) but more KRAS mutations and MSS CRC tumors were more prevalent [30].…”
Section: Discussionmentioning
confidence: 99%